Southernmost records of bottlenose dolphins, Tursiops truncatus - Prosser Goodall, Rae Natalie; Marchesi, María Constanza; Pimper, Lida Elena; Dellabianca, Natalia Andrea; Benegas, Luis G.; Torres, Monica Analia; Riccialdelli, Luciana (Polar Biology)
Bottlenose dolphins (Tursiops spp.) are cosmopolitan animals widely distributed in waters of both hemispheres. The taxonomy of Tursiops has long been controversial, with over 20 specific names being published, and subspecies and inshore/offshore forms being proposed. In the southwestern South Atlantic, subspecies T. truncatus truncatus and T. truncatus gephyreus were proposed for specimens along the coasts of Brazil, Uruguay, and Argentina. Sightings of bottlenose dolphins are common along the coast of Argentina as far south as the Province of Chubut (ca. 46°S). Here, we summarize and discuss the southernmost records of bottlenose dolphins. We cannot make inferences about the species or subspecies to which these animals belong given the small number of specimens. Future studies of external measurements, pigmentation, DNA, and isotopes from both sides of the continent should help clarify the situation off southern South America. Furthermore, research is needed to explore a possible link between an effect of general global warming and the Tursiops specimens found this far south. The sighting and specimens described here, at 53°S-nearly 55°S, are the southernmost records for the genus and extend the range of the species in the southern South Atlantic. Fil: Prosser Goodall, Rae Natalie. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Marchesi, María Constanza. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Pimper, Lida Elena. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ecología, Genética y Evolución; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Dellabianca, Natalia Andrea. Museo Acatushún de Aves y Mamíferos Marinos Australes; ...